Performance tests of ITER CS conductor samples from series production. (1st March 2023) - Breschi, M; Devred, A; Macioce, D; Mitchell, N
Abstract: The International Thermonuclear Experimental Reactor (ITER) magnet system is one of the most sophisticated superconducting magnet systems ever designed, with a stored energy of 51 GJ. The coils are wound from cable-in-conduit conductors made of superconducting and copper strands assembled into a multistage rope-type cable, inserted into a conduit of austenitic steel tubes. The ITER central solenoid (CS) works in pulsed mode, reaching a peak field of 13 T, thus allowing the induction of a high intensity current in the plasma of the ITER tokamak. This magnet consists of a stack of six modules which include around 125 t of Nb3 Sn strands. The production of all CS conductors has been completed and module manufacturing is well underway; throughout the production phase, samples were cut at the extremities of the conductor unit lengths to undergo quality control tests. About 25% of the conductor short samples were tested in current and field at cryogenic conditions at the SULTAN facility in Villigen, Switzerland. This work reports the comparative analysis of the short samples set of test results.